Functional consequences of lead and mercury exposomes in the heart - Ferreira, Gonzalo; Santander, Axel; Chavarría, Luisina; Cardozo, Romina; Savio, Florencia; Sobrevia, Luis [UNESP]; Nicolson, Garth L. (Elsevier, 2021)
Lead and mercury are heavy metals that are highly toxic to life forms. There are no known physiological processes that require them, and they do not have a particular threshold concentration to produce biologic damage. They are non-biodegradable, and they slowly accumulate in the environment in a dynamic equilibrium between air, water, soil, food, and living organisms. Their accumulation in the environment has been increasing over time, because they were not banned from use in anthropogenic industrial production. In their +2 cationic state they are powerful oxidizing agents with the ability to interfere significantly with processes that require specific divalent cations. Acute or chronic exposure to lead and mercury can produce multisystemic damage, especially in the developing nervous systems of children and fetuses, resulting in variety of neurological consequences. They can also affect the cardiovascular system and especially the heart, either directly through their action on cardiomyocytes or indirectly through their effects on innervation, humoral responses or blood vessel alterations. For example, heart function modified by these heavy metals are heart rate, contraction, excitability, and rhythm. Some cardiac molecular targets have been identified and characterized. The direct mechanisms of damage of these heavy metals on heart function are discussed. We conclude that exposome to these heavy metals, should be considered as a major relevant risk factor for cardiac diseases.
Keywords: Cardiac; Exposure; Intoxication; Lead; Mercury; Poisoning